2015
DOI: 10.1016/j.seizure.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome in patients with MRI-negative, PET-positive temporal lobe epilepsy

Abstract: Our results suggest that epilepsy surgery outcomes of MRI-negative, PET positive patients are similar to those of patients with MTS. This finding may aid in the selection of best candidates for epilepsy surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 45 publications
1
21
0
2
Order By: Relevance
“…Regarding 18-FDG-PET scan, the study revealed its high sensitivity for EZL in true-DRE patients where it showed regional brain hypometabolism congruent with the SOZ in 87.5% of 3-T MRI non-lesional patients. These results are in harmony with that of Capraz and colleagues [27] as well as Desarnaud and colleagues [28] who identified that interictal 18-FDG-PET scan is the most sensitive procedure for localization of TLE as well as SOZ of extratemporal origin even for MRI-negative patients.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding 18-FDG-PET scan, the study revealed its high sensitivity for EZL in true-DRE patients where it showed regional brain hypometabolism congruent with the SOZ in 87.5% of 3-T MRI non-lesional patients. These results are in harmony with that of Capraz and colleagues [27] as well as Desarnaud and colleagues [28] who identified that interictal 18-FDG-PET scan is the most sensitive procedure for localization of TLE as well as SOZ of extratemporal origin even for MRI-negative patients.…”
Section: Discussionsupporting
confidence: 88%
“…The mechanism underlying hypometabolism in epilepsy is believed to include neuronal loss, a decrease of synaptic density and diaschisis [2]. Hypometabolism observed in the ipsilateral temporal lobe is a finding that contributes to lateralization of epileptogenic focus in drug-resistant mesial temporal lobe epilepsy (TLE) patients undergoing surgical treatment [3][4][5][6][7][8]. The rate of ipsilateral temporal hypometabolism in TLE varies between 60% and 100% depending on the different analysis methods used and differences in patient groups in the studies [1].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of ipsilateral temporal hypometabolism in TLE varies between 60% and 100% depending on the different analysis methods used and differences in patient groups in the studies [1]. This finding also has a significant prognostic impact regarding patient outcomes [1,5,[7][8][9][10][11][12]. In a metaanalysis of 46 publications (between 1992 and 2006), it was shown that hypometabolism in the ipsilateral temporal lob in TLE patients had a predictive value of 86% for a good postsurgical outcome [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malformation of cortical development (MCD) and hippocampal sclerosis are the commonly encountered focal brain pathologies on surgical series in patients with MRI-negative epilepsy (2). Moreover, 40–80% of patients with MRI-negative epilepsy are likely to be seizure-free (78); whereas MRI-positive patients have a greater than two-fold surgical-success rate to achieve freedom from seizures, as compared to MRI-negative patients (9). …”
Section: Introductionmentioning
confidence: 99%